MORATORIUM HUKUMAN MATI DI INDONESIA PERSPEKTIF HAK ASASI MANUSIA - Fazari Zul Hasmi Kanggas; Meitria Cahyani; Aura Prasasti Subagja; Mohammad Syifa Urrosyidin (Journal of Indonesian Comparative of Syari'ah Law, 2025)
In Indonesia, the death penalty remains in effect, preceded by the implementation of a ten-year suspension (moratorium), as stipulated in Article 100 of the newly enacted Criminal Code (KUHP). This moratorium serves as an opportunity for the convicted individual to demonstrate rehabilitation before the sentence is carried out. Therefore, this study aims to examine the legal norms governing the death penalty moratorium and to analyze the human rights perspectives regarding the moratorium. This research employs a normative juridical method, utilizing data collection through literature study and qualitative analysis methods. The findings indicate that the legal norms concerning the death penalty moratorium, as outlined in Article 100 of Law Number 1 of 2023, establish a waiting period for execution, during which the behavior of the convicted individual is assessed. If the individual exhibits good conduct during this period, the death sentence may be commuted. Meanwhile, the death penalty moratorium aligns with the human rights concept, as the right to life is a non-derogable right. The 2007 UN Resolution on the moratorium was supported by a majority of countries, in accordance with Article 3 of the Universal Declaration of Human Rights (UDHR) and Article 6 of the International Covenant on Civil and Political Rights (ICCPR), while also considering the local wisdom of each nation. However, under Islamic law, qishas (retributive justice) must still be applied to resolve grievances between the perpetrator and the victim or their family, thereby preventing the recurrence of similar crimes.